2014
DOI: 10.1038/ncomms5846
|View full text |Cite
|
Sign up to set email alerts
|

The landscape of kinase fusions in cancer

Abstract: Human cancer genomes harbour a variety of alterations leading to the deregulation of key pathways in tumour cells. The genomic characterization of tumours has uncovered numerous genes recurrently mutated, deleted or amplified, but gene fusions have not been characterized as extensively. Here we develop heuristics for reliably detecting gene fusion events in RNA-seq data and apply them to nearly 7,000 samples from The Cancer Genome Atlas. We thereby are able to discover several novel and recurrent fusions invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

29
752
2
12

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 826 publications
(795 citation statements)
references
References 59 publications
29
752
2
12
Order By: Relevance
“…However, the kinase fusion KIF5B-MET has been identified in a case of lung adenocarcinoma, and it is feasible that this translocation event could potentially account for a significant portion of MET-driven oncogenesis (67). This fusion-driven activation of MET is most likely due to constitutive dimerization and is likely to be an actionable target for drug-induced inhibition, similar to other fusions in lung cancer such as those involving ALK, ROS1, and RET (67).…”
Section: Met Rearrangementmentioning
confidence: 99%
“…However, the kinase fusion KIF5B-MET has been identified in a case of lung adenocarcinoma, and it is feasible that this translocation event could potentially account for a significant portion of MET-driven oncogenesis (67). This fusion-driven activation of MET is most likely due to constitutive dimerization and is likely to be an actionable target for drug-induced inhibition, similar to other fusions in lung cancer such as those involving ALK, ROS1, and RET (67).…”
Section: Met Rearrangementmentioning
confidence: 99%
“…2,4 Interestingly, ALK fusions have also been described in esophageal cancer. 4 Of note, they can be targeted by ALK inhibitors, 4 highlighting the utility of fusions in guiding rational therapy for head and neck neoplasms.…”
Section: Thyroid Neoplasmsmentioning
confidence: 99%
“…In the majority of cases, a fusion partner provides dimerization domains that constitutively activate a kinase, thereby contributing to tumor development. 2 Thyroid carcinoma has also been shown to harbor a high percentage (70.3%) of in frame fusions compared to other malignancies. 4 Yoshihara et al found that tumor samples with recurrent in-frame fusion transcripts harbored less frequent gene mutations compared to samples without recurrent in frame fusion transcripts.…”
Section: Thyroid Neoplasmsmentioning
confidence: 99%
See 2 more Smart Citations